The South African nursing council: 50 years of professional self-regulation - W. J. Kotzé (AOSIS, 1995)
Self-regulation of the professions of nursing and midwifery became a reality in South Africa on 8 November 1944, when the first council meeting of the South African Nursing Council took place in Pretoria. Most appropriately, the opening speaker on this occasion was Mr Harry Gordon Lawrence, the Minister of Welfare and Demobilization, who had piloted the Nursing Act, No.45 of 1944, through Parliament. Exactly 50 years later, on 8 November 1994 the Council held its 108th meeting, this time in its own building, with a magnificent view of the venue where that historic first meeting took place - the west wing of the Union buildings.